THE EFFECTIVENESS OF CITRONELLA OIL MICROEMULSION AS A REPELLENT OF AEDES AEGYPTI MOSQUITO - SUBAGIYO, AGUS; WIDYANTO, ARIF; KHOMSATUN; ANANTA, ITA PRAMUDIA; KURNIAWAN, DHADHANG WAHYU (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to test the effectiveness of Citronella oil microemulsion as a repellent for the Aedes aegypti mosquito. Methods: The preparation of Citronella oil microemulsion was carried out through a high-speed homogenization technique. The microemulsion was formulated with a base of 100 g, consists of Citronella oil in several concentrations 5%, 10%, and 15%, emulsifier (Tween 80 and Tween 20) 10-20% by weight of citronella oil and 80-90% distilled water, made into six formulas (F). The microemulsions were then evaluated for the organoleptic, pH, and transmittance. Results: Based on the organoleptic test showed that F1 was selected as the best formula, a microemulsion with an active ingredient of Citronella oil in a concentration of 5% and an emulsifier 10%. The average pH was 5.35 according to normal skin pH (4-6.5) and the average size of the microemulsion is 2.42±0.09 µm and the PdI (polydispersity index) is 0.68±0.1. The protection power of F1 repellent was 90%, this result showed a significant difference (p-value of 0.005) as compared to Citronella oil without modification (70%), significantly different (p-value 0.001) with Tween 80–Tween 20 (10%) and not significantly different (p-value 0.145) with chemical repellent Product X (97%). Conclusion: Based on the result, it was concluded that the protective power of Citronella oil Microemulsion F1 was almost like chemical repellent Product X.